Physicochemical and biochemical coupling hardness removal process for coal gasification wastewater

Through the modified chitosan-nanocellulose composite template in the coal gasification wastewater treatment, the problem of difficult to remove hardness substances and organic pollutants in the prior art is solved, and the effect of efficient removal and resource utilization of sludge is achieved.

CN119859002AActive Publication Date: 2025-04-22SHANGHAI MINGNUO ENVIRONMENT TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510352641.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove hard substances and organic pollutants in coal gasification wastewater, and traditional treatment methods have problems such as low removal efficiency, large sludge production, and high operating costs.

Method used

The chitosan-nanocellulose composite template is used to modify the preloaded iron ions, doped biochar and construct a three-stage pore structure, and it is applied to the physical, chemical, biochemical and hard-coupled determination process of coal gasification wastewater to achieve adsorption of calcium and magnesium ions and degradation of organic pollutants.

Benefits of technology

It has achieved efficient removal of hardness substances and organic pollutants in coal gasification wastewater, reduced the cost of sludge treatment and disposal, and generated catalytically active calcium ferrite photocatalysts by calcining the sludge, realizing the resource utilization of sludge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859002A_ABST
    Figure CN119859002A_ABST
Patent Text Reader

Abstract

The invention provides a physicochemical and biochemical coupling hardness removal process for coal gasification wastewater, and belongs to the technical field of coal gasification wastewater treatment. Aiming at the characteristics of high hardness, high organic matter content and high ammonia nitrogen content of coal gasification wastewater, part of pollutants are removed through pretreatment; then, adding the modified chitosan-nanocellulose composite template into the pretreated wastewater, providing a nucleation site by iron ion preloading, enhancing adsorption and conductivity by charcoal doping, optimizing mass transfer by a three-level pore structure, efficiently adsorbing calcium and magnesium ions, and inducing to generate aragonite type calcium carbonate precipitate. And filling the precipitate serving as a biofilm carrier into anaerobic and aerobic two-stage biochemical reactors, and carrying out nitrification / denitrification treatment on the supernate. Finally, the sludge is deeply treated and converted into the calcium ferrite photocatalyst, and resource utilization is achieved. According to the method, COD, total hardness and ammonia nitrogen in the coal gasification wastewater can be effectively removed, the sludge recycling rate is high, and an efficient, economical and environment-friendly solution is provided for coal chemical wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coal gasification wastewater treatment, and in particular relates to a physicochemical and biochemical coupling hardness removal process for coal gasification wastewater. Background Art

[0002] With the rapid development of coal chemical industry, the discharge of coal gasification wastewater is increasing. Its high hardness, high organic matter and high ammonia nitrogen characteristics pose a serious threat to the environment.

[0003] Currently, common technologies for treating coal gasification wastewater include chemical precipitation, biological treatment, and membrane separation. However, traditional chemical precipitation suffers from low removal efficiency and high sludge production; biological treatment is poorly adapted to high-hardness wastewater and is easily inhibited; and membrane separation faces challenges such as membrane fouling and high operating costs.

[0004] Therefore, there is an urgent need to develop a coal gasification wastewater treatment technology that can efficiently remove hardness substances and organic pollutants and realize resource utilization. Summary of the Invention

[0005] The present invention overcomes the deficiencies of the prior art and provides a physical-chemical-biochemical coupled hardness removal process for coal gasification wastewater.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a physical-chemical-biochemical coupled hardness removal process for coal gasification wastewater, comprising the following steps: S1. Pre-treat wastewater; S2, adding chitosan-nanocellulose composite template to the pretreated wastewater to adsorb calcium and magnesium ions and induce the formation of aragonite-type calcium carbonate precipitation; S3, subjecting the wastewater containing precipitates in S2 to gradient stirring, and allowing it to stand to separate the supernatant and precipitates; S4, processing the precipitate in step S3 into a biofilm carrier, filling the biofilm carrier into an anaerobic and aerobic two-stage biochemical reactor, and passing the supernatant in S3 into the anaerobic and aerobic two-stage biochemical reactor for nitrification / denitrification treatment, and filtering to obtain treated water and sludge; S5. Deeply treat the sludge in S4.

[0007] Preferably, the preprocessing in S1 includes: S11, adding calcium hydroxide solution to the coal gasification wastewater, adjusting the pH and stirring; S12, coagulating and flocculating the wastewater treated in S11, and filtering the wastewater through an ultrafiltration membrane; S13, the wastewater treated in S12 is subjected to sedimentation separation, and the supernatant after separation is subjected to gas stripping.

[0008] Preferably, in step S2, the method for preparing the chitosan-nanocellulose composite template comprises: S210, adding chitosan powder to the acetic acid solution and stirring until completely dissolved to obtain a chitosan solution; S220, dispersing the nanocellulose in water to obtain a nanocellulose suspension; S230, mixing the chitosan solution and the nanocellulose suspension to form a mixed solution; S240, adding glutaraldehyde cross-linking agent to the mixed solution to initiate a cross-linking reaction; S250, drying the cross-linked mixed solution under vacuum to obtain a chitosan-nanocellulose composite template.

[0009] Preferably, the chitosan-nanocellulose composite template in step S2 is modified, including one or more of pre-loading iron ions, doping with biochar, and constructing a tertiary pore structure; wherein, the method of pre-loading iron ions is to immerse the composite template in an iron ion solution for adsorption; the method of doping with biochar is to mix and grind the biochar material with the composite template; the method of constructing a tertiary pore structure is to use silica nanospheres as a template to construct multi-level channels on the composite template.

[0010] Preferably, the method of preloading iron ions is further as follows: S211, dissolving ferric chloride in water to obtain an iron ion solution; S221, soaking the chitosan-nanocellulose composite template in an iron ion solution and stirring to allow the iron ions to be fully adsorbed onto the surface of the material; S231, washing the soaked composite template with water to remove unadsorbed iron ions; S241. Drying the washed composite template under vacuum to obtain an iron ion-loaded chitosan-nanocellulose composite template.

[0011] Preferably, the method of doping biochar further comprises: S221, pyrolyzing rice husks under a nitrogen atmosphere to obtain rice husk biochar, and grinding and sieving to obtain rice husk biochar nanosheets; S222, the chitosan-nanocellulose composite template is mixed with the rice husk biochar nanosheets, and the mixture is fully ground to uniformly disperse the biochar in the composite template.

[0012] Preferably, the method for constructing the tertiary pore structure is further as follows: S231, preparing silica nanospheres by sol-gel method; S232, mixing the chitosan-nanocellulose composite template and the silica nanospheres uniformly; S233, drying the mixture in a vacuum to fix the silica nanospheres on the composite template; S234. Soaking the cured composite material in a sodium hydroxide solution to remove the silica nanospheres to obtain a composite template having a tertiary pore structure.

[0013] Preferably, step S3 includes: S31, the wastewater containing precipitate in S2 is subjected to gradient stirring; the first stage is stirred at 120-180 rpm for 15-25 minutes; the second stage is stirred at 40-60 rpm for 8-12 minutes; S32, subjecting the wastewater treated in S31 to sedimentation separation, and dehydrating the sediment.

[0014] Preferably, step S4 includes: S41, processing the precipitate in S3 into a biofilm carrier, and filling the biofilm carrier into an anaerobic and aerobic two-stage biochemical reactor; S42, introducing the supernatant in S3 into an anaerobic reactor for anaerobic biological treatment; S43, introducing the effluent from the anaerobic reactor in S42 into the aerobic reactor for aerobic biological treatment.

[0015] Preferably, step S5 includes: S51, dewatering the sludge generated in S4; S52. calcining the dewatered sludge to generate a material with catalytic activity.

[0016] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention adopts a chitosan-nanocellulose composite template, which is modified by pre-loading iron ions, doping biochar and constructing a tertiary pore structure, and is applied to the physical-chemical-biochemical coupling hardness removal process of coal gasification wastewater, achieving efficient removal of hardness substances and organic pollutants and promoting the resource utilization of sludge.

[0017] (2) The modified composite template provided by the present invention has abundant calcium and magnesium ion adsorption sites and excellent mass transfer performance. Iron ions act as Lewis acid centers to promote calcium carbonate nucleation, biochar provides adsorption sites and electron transfer channels, and the tertiary pore structure optimizes mass transfer efficiency, allowing calcium and magnesium ions to be quickly and efficiently precipitated from wastewater to form aragonite-type calcium carbonate precipitates. Compared with traditional chemical precipitation methods, the present invention avoids the use of large amounts of chemical agents, reduces secondary pollution, and effectively reduces the risk of scaling in subsequent biochemical treatment units.

[0018] (3) The modified composite template provided by the present invention is attached to a large number of microorganisms, forming a highly active biofilm. The biochar provides microbial attachment sites and nutrients, and the ferric / ferrous ion redox couple promotes electron transfer, increasing microbial metabolic activity. This allows organic pollutants to be efficiently degraded by the microorganisms in the biofilm, reducing the COD in the wastewater. Compared with traditional biological treatment, the present invention improves the adaptability of biological treatment to high-hardness wastewater and reduces the cost of sludge treatment and disposal.

[0019] (4) The main components of the dehydrated sludge are aragonite-type calcium carbonate, precipitated iron-calcium-carbon complexes, and a small amount of organic matter. By calcining the dehydrated sludge, a catalytically active calcium ferrite photocatalyst is generated, which can be used for photocatalytic degradation of organic pollutants. Compared with traditional sludge landfill or incineration treatment, this method realizes the resource utilization of sludge, reduces environmental pollution, and achieves a win-win situation in economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments described in the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive efforts. Figure 1 This is a flow chart of a method for coupling physical, chemical and biochemical hardness removal from coal gasification wastewater; Figure 2 is a flow chart of a method for preparing a chitosan-nanocellulose composite template; Figure 3 is a flow chart of a method for preloading iron ions; Figure 4 is a flow chart of the method for doping biochar; Figure 5 is a flow chart of a method for constructing a tertiary pore structure. DETAILED DESCRIPTION

[0021] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0022] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present invention is not limited to the specific embodiments disclosed below.

[0023] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application. In addition, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0024] In the description of this application, it should be noted that, unless otherwise expressly specified or limited, the terms "installed," "connected," and "connected" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integral connections; they can refer to mechanical connections or electrical connections; they can refer to direct connections or indirect connections through an intermediate medium; and they can refer to internal connections between two components. Those skilled in the art will understand the specific meanings of the above terms in this application based on specific circumstances.

[0025] Unless otherwise stated, the raw materials involved in the present invention can be obtained commercially or prepared using methods well known to those skilled in the art.

[0026] Exemplary process: like Figure 1 As shown, a physical-chemical and biochemical coupled hardness removal process for coal gasification wastewater includes the following steps: S1. Pre-treat wastewater; S2, adding chitosan-nanocellulose composite template to the pretreated wastewater to adsorb calcium and magnesium ions and induce the formation of aragonite-type calcium carbonate precipitation; S3, subjecting the wastewater containing precipitates in S2 to gradient stirring, and allowing it to stand to separate the supernatant and precipitates; S4, processing the precipitate in step S3 into a biofilm carrier, filling the biofilm carrier into an anaerobic and aerobic two-stage biochemical reactor, and passing the supernatant in S3 into the anaerobic and aerobic two-stage biochemical reactor for nitrification / denitrification treatment, and filtering to obtain treated water and sludge; S5. Deeply treat the sludge in S4.

[0027] The pre-processing in step S1 includes: S11, adding calcium hydroxide solution to the coal gasification wastewater, adjusting the pH and stirring; S12, coagulating and flocculating the wastewater treated in S11, and filtering the wastewater through an ultrafiltration membrane; S13, the wastewater treated in S12 is subjected to sedimentation separation, and the supernatant after separation is subjected to gas stripping.

[0028] In step S11, coal gasification wastewater with a chemical oxygen demand of 2000-3000 mg / L and a total hardness of 1000-1500 mg / L is input into the reaction tank, and a calcium hydroxide solution with a mass concentration of 15-25% is added in an amount of 8-12 g / L; the pH of the wastewater is adjusted to 9.0-9.5 through interlocking control of the pH online monitor and the dosing pump to promote the conversion of bicarbonate ions into carbonate ions, increase the concentration of carbonate ions, stabilize the pH environment, and thus improve the efficiency of subsequent physicochemical treatment; the stirring speed is controlled to 60-80 rpm, the reaction temperature is 50-70°C, and the reaction time is 30-60 min.

[0029] By promoting the conversion of bicarbonate ions into carbonate ions, the pH environment is stabilized, and the efficiency of subsequent physical and chemical treatment is improved. At the same time, some calcium and magnesium ions are precipitated, reducing the concentration of calcium and magnesium ions in the wastewater and reducing the scaling risk of subsequent treatment units.

[0030] In step S12, the wastewater treated in S11 is rapidly mixed with a polyaluminium chloride coagulant at a dosage of 50-80 mg / L in a pipeline static mixer and then enters a slow flocculation zone for a flocculation time of 10-30 minutes; then enters a polyvinylidene fluoride ultrafiltration membrane module with a molecular weight cutoff of 72,000-88,000 Da, an operating pressure of 0.25-0.35 MPa, and a membrane flux of 20-30 L / (m²·h); the concentration of oil pollutants in the ultrafiltration water is controlled to be ≤25 mg / L, and the concentration of suspended solids is controlled to be ≤50 mg / L.

[0031] By adding polyaluminium chloride (PAC) coagulant, the suspended matter and colloidal particles in the wastewater are condensed into flocs, and separated by ultrafiltration membrane to remove the suspended matter and colloidal particles in the wastewater, reduce turbidity and SDI (pollution index), and prevent subsequent clogging of reverse osmosis membranes.

[0032] In step S13, the wastewater treated in step S12 is passed into an inclined plate sedimentation tank. A mechanical agitator is used at 60-80 rpm and a steam heating system is used to maintain a temperature of 50-70°C. Air stripping is combined with air stripping in a gas stripping tower to promote the conversion of ammonium ions into volatile ammonia water. The effluent ammonia nitrogen concentration is controlled to ≤300 mg / L, and the tail gas is treated in an acid absorption tower. At 50°C, the solubility of ammonia is reduced by 60% compared to 25°C. Increasing the temperature reduces the solubility of ammonia.

[0033] By heating the wastewater and stripping it with air through a stripping tower, the ammonium ions in the wastewater are converted into ammonia gas, which is then absorbed by an acid absorption tower to reduce the ammonia nitrogen concentration in the wastewater.

[0034] In step S2, the wastewater treated in step S1 is input into a physicochemical reaction tank, and a carboxylated chitosan-nanocellulose composite template is added at a dosage of 1.0-2.0 g / L of wastewater; the stirring speed is controlled to 100-200 rpm, the reaction temperature is 30-40°C, and the reaction time is 20-40 min; calcium and magnesium ions are selectively adsorbed through the chelation effect of carboxyl groups and calcium ions, thereby inducing the formation of aragonite-type calcium carbonate precipitates.

[0035] The chitosan-nanocellulose composite template provides adsorption sites for calcium and magnesium ions, with the carboxyl groups (-COOH) on the chitosan chelating with them. Nanocellulose acts as a carrier, increasing the specific surface area and providing a template for crystal nucleation growth.

[0036] Specifically, if Figure 2 As shown, the preparation method of the chitosan-nanocellulose composite template includes: S210, dissolving chitosan powder in 1-2% acetic acid solution to prepare a chitosan solution with a mass concentration of 1-2%, and stirring until completely dissolved; S220, dispersing the nanocellulose in deionized water, and uniformly dispersing the nanocellulose by ultrasonic treatment to prepare a nanocellulose suspension with a mass concentration of 0.4-0.6%; S230, mixing the chitosan solution and the nanocellulose suspension in a mass ratio of 3:1 to 4:1, and stirring for 15-30 minutes to fully mix the two materials; S240, adding glutaraldehyde crosslinking agent to the mixed solution, wherein the amount of glutaraldehyde is 0.8-1.2% of the mass of chitosan, and continuing stirring for 1-2 hours to allow the chitosan and nanocellulose to undergo a crosslinking reaction; S250, pouring the cross-linked mixture into a culture dish, and vacuum drying at 50-60° C. for 18-24 hours to obtain a chitosan-nanocellulose composite template.

[0037] The amino and hydroxyl groups on the chitosan molecular chain react with glutaraldehyde to form stable chemical bonds, connecting the chitosan and nanocellulose. Nanocellulose increases the specific surface area and porosity of the composite material, providing more space for the adsorption of calcium and magnesium ions.

[0038] The chitosan-nanocellulose composite template in step S2 is further modified by one or more of preloading iron ions, doping with biochar, and constructing a tertiary pore structure. Preloading iron ions involves immersing the composite template in an iron ion solution for adsorption; doping with biochar involves mixing and grinding the biochar material with the composite template; and constructing a tertiary pore structure involves constructing multi-level pore channels on the composite template using silica nanospheres as a template.

[0039] The chitosan-nanocellulose composite template is immersed in an iron ion solution, allowing the iron ions to adsorb onto the surface of the material. Ion exchange occurs between the iron ions and the carboxyl groups on the chitosan, securing the iron ions within the material. Preloading the composite template with 0.5-1.0wt% iron ions improves the mechanical strength and stability of the precipitate, enhances electron transfer, and promotes the nucleation and growth of calcium carbonate.

[0040] Specifically, if Figure 3 As shown, the method of preloading iron ions includes: S211, dissolving ferric chloride in deionized water to prepare an iron ion solution with a concentration of 0.07-0.13 mol / L; S221, soaking the chitosan-nanocellulose composite template in an iron ion solution with a solid-liquid ratio of 1:20 to 2:20, and stirring at room temperature for 1-2 hours to allow the iron ions to be fully adsorbed onto the surface of the material; S231, washing the impregnated composite template with deionized water several times to remove unadsorbed iron ions; S241, vacuum drying the washed composite template at 50-60° C. for 18-24 hours to obtain an iron ion-loaded chitosan-nanocellulose composite template.

[0041] Iron ions coordinate with carboxyl or amino groups on chitosan, forming stable chemical bonds. Iron ions act as Lewis acid centers, promoting the nucleation and growth of calcium carbonate. Furthermore, the ferric / ferrous redox couple promotes electron transfer, enhancing the electrochemical activity of the material.

[0042] Biochar powder is added during the preparation of chitosan-nanocellulose composites to form a composite structure. By doping with 10-20nm thick rice husk biochar nanosheets, the specific surface area and pore volume of the material are further increased, thereby increasing the number of adsorption sites.

[0043] Specifically, if Figure 4 As shown, methods of biochar incorporation include: S221, pyrolyzing rice husks at 300-700°C under a nitrogen atmosphere to obtain rice husk biochar. Grinding the obtained biochar through a 180-200 mesh sieve to obtain rice husk biochar nanosheets; S222. Mix the iron ion loaded chitosan-nanocellulose composite template and the rice husk biochar nanosheets in a mass ratio of 100:3 to 100:7, and grind them thoroughly to uniformly disperse the biochar in the composite material.

[0044] Oxygen-containing functional groups (-COOH, -OH) on the biochar surface interact with chitosan or nanocellulose, enhancing the binding force of the materials. The porous structure of biochar provides more adsorption sites, improving the material's adsorption performance. The biochar's electrical conductivity promotes electron transfer, enhancing the material's electrochemical activity.

[0045] A tertiary pore structure is constructed using mesoporous silica nanospheres on a chitosan-nanocellulose composite template, resulting in micropores (less than 2 nm), mesopores (2 to 50 nm), and macropores (greater than 50 nm). The micropores provide a high surface area and increase adsorption sites; the mesopores provide mass transfer channels and accelerate ion diffusion; and the macropores reduce mass transfer resistance, facilitating the entry of wastewater into the material.

[0046] Specifically, if Figure 5 As shown, the method for constructing the tertiary pore structure includes: S231, preparing mesoporous silica nanospheres with an average particle size of 40-60 nm by a sol-gel method; S232, mixing the chitosan-nanocellulose composite template and the mesoporous silica nanospheres in a mass ratio of 4:1 to 6:1; S233, drying the mixture in a vacuum drying oven at 50-60° C. for 2-3 hours to fix the mesoporous silica nanospheres in the composite material; S234. Soaking the cured composite material in a sodium hydroxide solution to remove the mesoporous silica nanosphere template to obtain a composite template having a tertiary pore structure.

[0047] Mesoporous silica nanospheres form the skeleton structure of the composite material, leaving mesopores and macropores after the template is removed. Chitosan, nanocellulose, and biochar fill the gaps between the mesopores and macropores, forming micropores.

[0048] Step S3 includes: S31, the wastewater containing precipitate in S2 is subjected to gradient stirring; the first stage is stirred at 120-180 rpm for 15-25 minutes; the second stage is stirred at 40-60 rpm for 8-12 minutes; S32, subjecting the wastewater treated in S31 to sedimentation separation, and dehydrating the sediment.

[0049] In step S31, the wastewater containing precipitation in S2 is introduced into a gradient agitator, and the first stage high-speed stirring improves the liquid phase mass transfer rate, promotes the diffusion of calcium and magnesium ions to the composite template surface, and accelerates the formation of crystal nuclei. The high shear force brought by high-speed stirring helps to disperse the crystal nuclei and prevents local supersaturation from causing amorphous precipitation. The second stage low-speed stirring reduces the liquid phase mass transfer rate, slows down the crystal growth rate, and makes the crystal grow slowly under thermodynamic control, which is conducive to forming more stable and higher crystallinity aragonite calcium carbonate. Low-speed stirring reduces the collision frequency between crystals and suppresses crystal agglomeration.

[0050] In step S32, the wastewater, after gradient agitation in step S31, is introduced into a static sedimentation tank. After settling for 1-2 hours, a layered suction device separates the supernatant from the sediment. The sediment is then dehydrated using a screw extruder, controlling the pressure gradient to 0.5-2.0 MPa. The dehydrated sludge has a moisture content of ≤70%. The applied pressure forces the water in the sediment to drain through the pores. The shear force generated by the screw extruder helps disrupt the flocculated structure of the sludge, releasing water.

[0051] The main components of the precipitate are aragonite calcium carbonate, precipitated iron-calcium-carbon complex and a small amount of organic matter.

[0052] Step S4 includes: S41, processing the precipitate in S3 into a biofilm carrier, and filling the biofilm carrier into an anaerobic and aerobic two-stage biochemical reactor; S42, introducing the supernatant in S3 into an anaerobic reactor for anaerobic biological treatment; S43, introducing the effluent from the anaerobic reactor in S42 into the aerobic reactor for aerobic biological treatment.

[0053] In step S41, the precipitate produced in S3 is crushed into 1-5 mm particles and filled into the anaerobic and aerobic two-stage biochemical reactors as biofilm carriers with a filling rate of 20%-40%; the surface conductivity of the carrier is ≥5S / m, and electron transfer is mediated by the ferric ion / ferrous ion redox couple.

[0054] Precipitated iron-calcium-carbon complexes are formed by the interaction of ferric / ferrous ions, calcium carbonate, and biochar. They exhibit excellent electrical conductivity and promote electron transfer between microbial cells, forming an extracellular electron transfer network and enhancing the degradation efficiency of organic matter. Biochar, with its porous structure and large surface area, can adsorb organic matter and nutrients, promoting the attachment and growth of microorganisms on the carrier surface and forming a biofilm. The ferric / ferrous ion redox pair mediates electron transfer, promoting microbial metabolic activity and increasing the degradation rate of organic matter.

[0055] In step S42, the dissolved oxygen in the reactor is controlled to near 0 mg / L (anaerobic environment), the temperature is 30-35°C, and the hydraulic retention time is 12-24 hours. Under anaerobic conditions, anaerobic microorganisms decompose refractory organic matter into intermediate products such as small-molecule organic acids and alcohols. Denitrification is then carried out to convert nitrates into nitrogen gas. Anaerobic microorganisms include but are not limited to methanogens, fermentative bacteria, and denitrifying bacteria.

[0056] In step S43, the dissolved oxygen in the reactor is controlled at 1.5-2.5 mg / L, the temperature is 30-35°C, and the hydraulic retention time is 6-12 hours. Under aerobic conditions, the electroactive bacteria are enriched, further degrading organic matter and undergoing nitrification, converting ammonia nitrogen into nitrate. The electroactive bacteria include, but are not limited to, Geobacter and Shewanella; and the nitrifying bacteria include, but are not limited to, Nitrosobacter and Nitrobacter.

[0057] Step S5 includes: S51, dewatering the sludge generated in S4; S52. calcining the dewatered sludge to generate a material with catalytic activity.

[0058] In step S51, a periodic high-voltage electric field is applied to the sludge in S4, with an electric field strength of 3-6 kV / cm, a pulse width of 20-50 μs, a pulse interval of 0.5-1.5 s, and a dehydration time of 15-25 min; selective dehydration is achieved by utilizing the low dielectric constant characteristics of aragonite calcium carbonate.

[0059] Under the influence of a high-voltage electric field, water molecules become polarized, generating electroosmosis and electrophoresis, which promote the migration of water from the sludge. Aragonite calcium carbonate has a low dielectric constant, which reduces electric field energy loss and improves dehydration efficiency. Furthermore, calcium carbonate crystals act as a skeleton, strengthening the sludge's structural strength and reducing the breakage of sludge particles during dehydration. The pulsed electric field can also disrupt sludge cell walls, releasing water within the cells and improving dehydration efficiency.

[0060] In step S52, the dehydrated sludge is placed in a muffle furnace and calcined at 250-350°C for 1-3 hours to generate a calcium ferrite photocatalyst.

[0061] Under high temperature conditions, the organic matter in the sludge is oxidized and decomposed, and calcium and iron form calcium ferrite crystals. Calcium ferrite is a spinel ferrite with a divalent metal ion (calcium ion) at the A site and a trivalent metal ion (iron ion) at the B site. Calcium ferrite exhibits visible light catalytic activity, absorbing light energy and converting it into chemical energy for the degradation of organic pollutants.

[0062] Example 1

[0063] A physical-chemical-biochemical coupling hardness removal process for coal gasification wastewater comprises the following steps: S11. Feed the coal gasification wastewater into the reaction tank and add 10 g / L of a 20% calcium hydroxide solution. Adjust the wastewater pH to 9.2 using an online pH monitor interlocked with a dosing pump. Maintain a stirring speed of 70 rpm, a reaction temperature of 60°C, and a reaction time of 45 minutes.

[0064] S12. The wastewater is rapidly mixed with a polyaluminium chloride coagulant at a dosage of 65 mg / L in a pipeline static mixer and then enters the slow flocculation zone with a flocculation time of 20 minutes; then it enters the polyvinylidene fluoride ultrafiltration membrane module with a molecular weight cutoff of 80,000 Da, with an operating pressure of 0.3 MPa and a membrane flux of 25 L / (m²·h).

[0065] S13. In the inclined plate sedimentation tank, the temperature is maintained at 60°C by a mechanical stirring device at a speed of 70 rpm and a steam heating system, combined with air stripping in the stripping tower, and the tail gas is treated in an acid absorption tower.

[0066] S2. The pretreated wastewater was fed into the physicochemical reaction tank. A chitosan-nanocellulose composite template, preloaded with iron ions, doped with biochar, and modified with a tertiary pore structure, was added at a dosage of 1.5 g / L of wastewater. The stirring speed was controlled at 150 rpm, the reaction temperature at 35°C, and the reaction time was 30 minutes.

[0067] S31, in the first stage, stirring was performed at 150 rpm for 20 min to promote the diffusion and nucleation of calcium and magnesium ions. In the second stage, stirring was performed at 50 rpm for 10 min.

[0068] S32. After settling for 1.5 hours, the upper clear liquid and the lower sediment were separated by a layered suction device. The sediment was dehydrated by screw extrusion, and the pressure gradient was controlled at 1.25 MPa.

[0069] S41. Crushing the precipitate produced in the precipitation and separation step of S3 into 3 mm particles, and filling the precipitate into the anaerobic and aerobic two-stage biochemical reactors as biofilm carriers, with a filling rate of 20%.

[0070] S42. Introduce the wastewater into the anaerobic reactor, control the dissolved oxygen in the anaerobic reactor to be close to 0 mg / L, the temperature to be 32.5°C, and the hydraulic retention time to be 18 hours.

[0071] S43. The effluent from the anaerobic reactor is introduced into the aerobic reactor, and the dissolved oxygen in the aerobic reactor is controlled to be 2.0 mg / L, the temperature to be 32.5°C, and the hydraulic retention time to be 9 hours.

[0072] S51. Apply a periodic high-voltage electric field to the sediment with an electric field strength of 4.5 kV / cm, a pulse width of 35 μs, a pulse interval of 1 s, and a dehydration time of 20 min.

[0073] S52. Place the dehydrated sludge in a muffle furnace and calcine it at 300° C. for 2 h to generate a calcium ferrite photocatalyst.

[0074] The preparation method of the chitosan-nanocellulose composite template includes: S210. Dissolve chitosan powder in 1% acetic acid solution to prepare a chitosan solution with a mass concentration of 1%, and stir until completely dissolved.

[0075] S220, dispersing the nanocellulose in deionized water, and uniformly dispersing the nanocellulose by ultrasonic treatment to prepare a nanocellulose suspension with a mass concentration of 0.5%.

[0076] S230, mixing the chitosan solution and the nanocellulose suspension in a mass ratio of 3:1 and stirring for 30 minutes.

[0077] S240, adding glutaraldehyde crosslinking agent to the mixed solution, the amount of glutaraldehyde used is 1% of the mass of chitosan, and continuing stirring for 2 hours.

[0078] S250, pouring the cross-linked mixture into a culture dish, and vacuum drying at 60° C. for 24 h to obtain a chitosan-nanocellulose composite template.

[0079] Methods for preloading iron ions include: S211. Dissolve ferric chloride in deionized water to prepare an iron ion solution with a concentration of 0.10 mol / L.

[0080] S221. Soak the chitosan-nanocellulose composite template in an iron ion solution, control the solid-liquid ratio to 1:20, and stir for 2 hours.

[0081] S231, washing the immersed composite template with deionized water for several times.

[0082] S241. The washed composite template is vacuum-dried at 60° C. for 24 h to obtain an iron ion-loaded chitosan-nanocellulose composite template.

[0083] Methods for doping biochar include: S221. Pyrolyze rice husks at 500° C. under a nitrogen atmosphere to obtain rice husk biochar. Grind the rice husk biochar through a 200-mesh sieve to obtain rice husk biochar nanosheets.

[0084] S222. The iron ion-loaded chitosan-nanocellulose composite template and the rice husk biochar nanosheets are mixed in a mass ratio of 100:5 and fully ground.

[0085] Methods for constructing a tertiary pore structure include: S231. Prepare mesoporous silica nanospheres with an average particle size of 50 nm using a sol-gel method.

[0086] S232. Evenly mix the chitosan-nanocellulose composite template and the mesoporous silica nanospheres in a mass ratio of 5:1.

[0087] S233. Dry the mixture in a vacuum drying oven at 60° C. for 3 h to fix the mesoporous silica nanospheres in the composite material.

[0088] S234. Soak the cured composite material in a sodium hydroxide solution to remove the mesoporous silica nanosphere template.

[0089] Example 2

[0090] In this embodiment, the difference from Example 1 is that the concentration of the ferric chloride solution in step S211 is adjusted to 0.07 mol / L, and the remaining steps are the same as in Example 1.

[0091] Example 3

[0092] The difference from Example 1 is that the concentration of the ferric chloride solution in step S211 is adjusted to 0.13 mol / L, and the remaining steps are the same as Example 1.

[0093] Example 4

[0094] In this embodiment, different from Example 1, the mass ratio of the iron ion-loaded chitosan-nanocellulose composite template to the rice husk biochar nanosheets in step S222 is adjusted to 100:3, and the remaining steps are the same as Example 1.

[0095] Example 5

[0096] In this embodiment, different from Example 1, the mass ratio of the iron ion-loaded chitosan-nanocellulose composite template to the rice husk biochar nanosheets in step S222 is adjusted to 100:7, and the remaining steps are the same as Example 1.

[0097] Example 6

[0098] In this embodiment, different from Example 1, the mass ratio of the chitosan-nanocellulose composite template to the mesoporous silica nanospheres in step S232 is adjusted to 4:1, and the remaining steps are the same as in Example 1.

[0099] Example 7

[0100] In this embodiment, the difference from Example 1 is that in step S232, the mass ratio of the chitosan-nanocellulose composite template to the mesoporous silica nanospheres is adjusted to 6:1, and the remaining steps are the same as in Example 1.

[0101] Example 8

[0102] In this embodiment, unlike in Example 1, only the chitosan-nanocellulose composite template is added in S2, and no pre-loading of iron ions, doping of biochar, or construction of a tertiary pore structure modification is performed. The remaining steps are the same as in Example 1.

[0103] Experimental Example 1 Experimental purpose: To verify the synergistic effect of pre-loading iron ions, doping biochar and constructing tertiary pore structure modification on the physical-chemical-biochemical coupling hardness removal process of coal gasification wastewater.

[0104] Experimental object: Wastewater discharged from a coal gasification plant, with an initial COD of 2500 mg / L, an initial total hardness of 1250 mg / L, and an initial ammonia nitrogen of 300 mg / L.

[0105] Experimental steps: i. Pretreat the wastewater according to steps S11, S12, and S13 in Example 1.

[0106] ii. Chitosan-nanocellulose composite templates were prepared according to steps S210-S250 of Example 1. The prepared chitosan-nanocellulose composite templates were divided into seven groups and modified by preloading iron ions, doping with biochar, and constructing a tertiary pore structure according to the methods of Examples 1-7 to prepare different modified composite templates. In Example 8, the chitosan-nanocellulose composite templates were used directly without any treatment.

[0107] iii. The pretreated wastewater was fed into eight physicochemical reaction tanks, and the corresponding composite template was added according to the method of Examples 1-8; the stirring speed was controlled at 150 rpm, the reaction temperature was 35°C, and the reaction time was 30 min.

[0108] iv. The suspensions in the eight physicochemical reaction tanks were transferred to sedimentation tanks and subjected to precipitation separation according to steps S31 and S32 of Example 1.

[0109] v. Each of the eight groups of sediment was crushed into 3 mm particles and used as biofilm carriers in eight anaerobic and aerobic two-stage biochemical reactors, with a fill rate of 20%. The anaerobic reactors were maintained at a dissolved oxygen concentration close to 0 mg / L, a temperature of 32.5°C, and a hydraulic retention time of 18 hours. The aerobic reactors were maintained at a dissolved oxygen concentration of 2.0 mg / L, a temperature of 32.5°C, and a hydraulic retention time of 9 hours.

[0110] vi. The eight groups of biochemically treated sludge were subjected to pulsed electric field-assisted dehydration according to step S51 in Example 1; the eight groups of dehydrated sludge were placed in a muffle furnace and calcined according to step S52 in Example 1 to generate calcium ferrite photocatalyst.

[0111] vii. Measure the COD, total hardness, and ammonia nitrogen content of the wastewater after treatment with S1, S2, S3, and S4 in each of the eight experimental groups. Calculate the COD, total hardness, and ammonia nitrogen removal rates, as well as the sludge reduction and resource utilization rates for each of the eight experimental groups.

[0112] COD removal rate = (raw water COD - COD after S4 treatment) / raw water COD × 100% Total hardness removal rate = (total hardness of raw water - total hardness after S4 treatment) / total hardness of raw water × 100% Ammonia nitrogen removal rate = (ammonia nitrogen in raw water - ammonia nitrogen after S4 treatment) / ammonia nitrogen in raw water × 100% Sludge resource utilization rate = sludge volume utilized as a resource / initial sludge volume × 100% The results are shown in the following table: Table 1 Experimental data Table 1

[0113] Table 2 Experimental data Table 2

[0114] Experimental data show that after S2 treatment, the COD, total hardness and ammonia nitrogen concentrations of each experimental group were reduced to varying degrees, among which the reduction in groups 1-7 was significantly greater than that in group 8 (unmodified group). After treatment with S3 and S4, the pollutant concentrations of each group were further reduced, and the effluent concentration and removal rate after S4 treatment showed obvious differences between the groups. Among them, Example 1 showed the best treatment effect, reaching the highest values ​​in COD, total hardness and ammonia nitrogen removal rates and sludge resource utilization rates. The treatment effects of other modified groups showed certain fluctuations due to different modification ratios, but they were all better than the unmodified group.

[0115] In general, iron ion preload increases the surface charge of the template, stabilizes biochar adsorption, enhances the mechanical strength of the template, and maintains the tertiary pore structure; however, excessive iron ions inhibit microbial activity, and too little cannot fully exert the nucleation effect. Biochar provides a dispersion environment for iron ions, improves their activity, enhances the mechanical strength of the template, and assists in the integrity of the tertiary pore structure; however, excessive biochar occupies too much pore space, affecting mass transfer, and too little cannot provide enough adsorption sites. The tertiary pore structure provides a larger surface area and porosity for iron ions and biochar, increases adsorption capacity and reaction rate, and reduces mass transfer resistance; however, too much tertiary pore structure reduces template strength, and too little leads to limited improvement in mass transfer efficiency. The three modifications work synergistically, making the modified group superior to the unmodified group, and there is an optimal ratio.

[0116] Specifically, the complex synergistic effects among iron ion preloading, biochar doping, and tertiary pore structure construction are reflected in the regulation of charge transfer, surface active sites, and microenvironment.

[0117] The introduction of iron ions modifies the electronic structure of the composite material, promoting charge transfer. Iron ions are not only excellent Lewis acid centers, capable of adsorbing negatively charged carbonate ions and promoting the nucleation of calcium carbonate, but they also significantly affect the electron cloud density distribution on the biochar surface. By altering the electronic structure of the biochar surface, iron ions can improve the biochar's adsorption capacity for organic pollutants and enhance the efficiency of electron transfer between the biochar and microorganisms. This enhanced electron transfer is particularly important for aerobic denitrification, promoting the reduction of nitrate to nitrogen gas. However, excessive iron ions form an oxide layer on the biochar surface, reducing its conductivity and inhibiting electron transfer. Excessive iron ions cannot effectively alter the biochar's electronic structure, resulting in limited improvement in electron transfer efficiency. Furthermore, iron ions can form coordination bonds with amino or hydroxyl groups on chitosan, affecting the distribution of biochar within the three-dimensional pores and controlling its exposure, thereby affecting its adsorption properties.

[0118] The π-electron conjugated structure of biochar can form charge transfer complexes with iron ions, further stabilizing the presence of iron ions and reducing their loss. More importantly, the porous structure of biochar can effectively regulate the microenvironment of the tertiary pores. By changing the pore size distribution and surface chemical properties of biochar, the humidity, pH value, and redox potential within the pores can be precisely controlled, thereby optimizing the growth environment of microorganisms and enhancing the activity of biofilms. However, excessive biochar blocks the tertiary pores and hinders mass transfer; too little biochar cannot effectively regulate the pore microenvironment, and the improvement of microbial activity is limited.

[0119] The tertiary pore structure not only provides a larger specific surface area, but more importantly, it creates a multi-scale reaction space. Micropores can enrich pollutants through capillary condensation and increase the concentration of local reactants. Mesopores can promote the diffusion of reaction intermediates and accelerate the reaction rate. Macropores can reduce mass transfer resistance and improve the transmission efficiency of reactants and products. In addition, the tertiary pore structure can also affect the exposure degree and active site distribution of iron ions and biochar. By controlling the size and shape of the pores, specific types of active sites can be selectively exposed, thereby improving the selectivity and catalytic efficiency of the composite material. However, too many tertiary pores result in too thin pore walls, which are easy to collapse and reduce structural stability; too few tertiary pores cannot effectively improve mass transfer and the utilization rate of active sites is low.

[0120] The above description is based on the ideal embodiment of the present invention. Based on the above description, relevant personnel can make various changes and modifications without departing from the technical scope of this invention. The technical scope of this invention is not limited to the content of the specification and must be determined according to the scope of the claims.

Claims

1. A physical-chemical-biochemical coupling hardness removal process for coal gasification wastewater, characterized in that: The following steps are involved: S1. Pre-treat wastewater; S2, adding chitosan-nanocellulose composite template to the pretreated wastewater to adsorb calcium and magnesium ions and induce the formation of aragonite calcium carbonate precipitation; S3, subjecting the wastewater containing precipitate in S2 to gradient stirring, and allowing it to stand to separate the supernatant and precipitate; S4, treating the precipitate in step S3 to prepare a biofilm carrier, filling it into an anaerobic and aerobic two-stage biochemical reactor, and passing the supernatant in S3 into an anaerobic and aerobic two-stage biochemical reactor for nitrification / denitrification treatment, and filtering to obtain treated water and sludge; S5. Deeply treat the sludge in S4.

2. The process according to claim 1, characterized in that Preprocessing in S1 includes: S11, adding calcium hydroxide solution to the coal gasification wastewater, adjusting the pH and stirring; S12, coagulating and flocculating the wastewater treated in S11, and filtering the wastewater through an ultrafiltration membrane; S13, subjecting the wastewater treated by S12 to sedimentation separation, and subjecting the separated supernatant to gas stripping.

3. The process according to claim 1, characterized in that In step S2, the preparation method of the chitosan-nanocellulose composite template includes: S210, adding chitosan powder to the acetic acid solution, stirring until completely dissolved, to obtain a chitosan solution; S220, dispersing the nanocellulose in water to obtain a nanocellulose suspension; S230, mixing and stirring the chitosan solution and the nanocellulose suspension to form a mixed solution; S240, adding glutaraldehyde cross-linking agent to the mixed solution to initiate a cross-linking reaction; S250, drying the cross-linked mixed solution under vacuum to obtain a chitosan-nanocellulose composite template.

4. The process according to claim 1, characterized in that The chitosan-nanocellulose composite template in step S2 is modified, including one or more of pre-loading iron ions, doping with biochar, and constructing a tertiary pore structure; wherein the method of pre-loading iron ions is to immerse the composite template in an iron ion solution for adsorption; the method of doping with biochar is to mix and grind the biochar material with the composite template; the method of constructing a tertiary pore structure is to use silica nanospheres as a template and construct multi-level channels on the composite template.

5. The process according to claim 4, characterized in that The method of preloading iron ions is further as follows: S211, dissolving ferric chloride in water to obtain an iron ion solution; S221, immersing the chitosan-nanocellulose composite template in an iron ion solution and stirring to allow the iron ions to be fully adsorbed onto the surface of the material; S231, washing the immersed composite template with water to remove unabsorbed iron ions; S241, drying the washed composite template under vacuum to obtain an iron ion-loaded chitosan-nanocellulose composite template.

6. The process according to claim 4, characterized in that The method of doping biochar is further: S221, pyrolyzing rice husk under a nitrogen atmosphere to obtain rice husk biochar, grinding and sieving to obtain rice husk biochar nanosheets; S222, the chitosan-nanocellulose composite template is mixed with the rice husk biochar nanosheets, and fully ground to make the biochar evenly dispersed in the composite template.

7. The process according to claim 4, characterized in that The method of constructing the tertiary pore structure is further as follows: S231, preparing silica nanospheres by sol-gel method; S232, mixing the chitosan-nanocellulose composite template and the silica nanospheres uniformly; S233, drying the mixture in a vacuum to fix the silica nanospheres on the composite template; S234, soaking the cured composite material in a sodium hydroxide solution to remove the silica nanospheres, thereby obtaining a composite template having a tertiary pore structure.

8. The process according to claim 1, characterized in that Step S3 includes: S31, the wastewater containing precipitate in S2 is subjected to gradient stirring; in the first stage, stirring is performed at 120-180 rpm for 15-25 min; in the second stage, stirring is performed at 40-60 rpm for 8-12 min; S32, subjecting the wastewater treated in S31 to sedimentation separation, and dehydrating the sediment.

9. The process according to claim 1, characterized in that Step S4 includes: S41, processing the precipitate in S3 to prepare a biofilm carrier, and filling the biofilm carrier into an anaerobic and aerobic two-stage biochemical reactor; S42, introducing the supernatant in S3 into an anaerobic reactor for anaerobic biological treatment; S43, introducing the effluent from the anaerobic reactor in S42 into the aerobic reactor for aerobic biological treatment.

10. The process according to claim 1, characterized in that Step S5 includes: S51, dewatering the sludge produced in S4; S52, calcining the dewatered sludge to generate a material with catalytic activity.

Citation Information

Patent Citations

  • Catalyst for oxidation and decomposition of organic pollutants in water with ozone and method thereof for catalyzing sewage treatment with ozone

    CN102151567A

  • Coal chemical production wastewater treatment and high-efficiency recycling process and special system thereof

    CN104386881A

  • Method for preparing chitosan nanocellulose-base composite spherical adsorption material

    CN106268679A

  • Horizontal rotary drum reactor for aerobic biological treatment of wastewater and application of horizontal rotary drum reactor

    CN110902815A

  • Biochar suspension carrier with synchronous short-cut nitrification and denitrification functions and preparation method thereof

    CN117682663A